Design of Active Integrated GNSS Antenna Based on the Impedance Transforming Quadrature Four-Feed Network - Yao Wang; Hongmei Liu; Shuo Li; Zhongbao Wang; Shaojun Fang (International Journal of Antennas and Propagation, 2023)
In the paper, a wideband miniaturized impedance-transforming quadrature four-feed network with a flat output phase difference is presented and applied to the design of an active integrated GNSS antenna where no extra impedance matching circuit is needed. The features of impedance transformation and flat output phase difference are achieved by the proposed miniaturized rat-race coupler. When combining the proposed rat-race coupler with two trans-directional (TRD) couplers, a four-feed network with stable sequential quadrature phase shifts is obtained in the whole GNSS band. Since the quadrature four-feed network has the feature of impedance transformation, integration with a low-noise amplifier (LNA) can be realized without extra impedance matching circuits, which reduce the overall size and losses. For validation, a simple rectangular patch is applied as the radiator, and the active prototype is fabricated. Measurement results show that over the entire GNSS band from 1.164 GHz to 1.610 GHz, the miniaturized integrated antenna exhibits a return loss of more than 10 dB, an axial ratio of less than 3 dB axial ratio, and a gain of greater than 16 dBic.